Kinetics of aspartame precursor synthesis catalysed by Pseudomonas aeruginosa elastase - Lee, Kong H.; Lee, Pat M.; Siaw, Yew S.; Morihara, Kazuyuki (Society of Chemical Industry, 1993)
Elastase isolated from Pseudomonas aeruginosa IFO 3455 was found to be an efficient protease to catalyse the synthesis of N‐benzyloxycarbonyl‐aspartyl‐phenylalanine methyl ester, the precursor of the dipeptide sweetener, aspartame. The influence of methanol as a cosolvent in this synthetic reaction was investigated. It was found that the synthesis of the dipeptide precursor was most efficient in 25% (v/v) methanol, pH 7·0 at about 25°C for a reaction time of about 3 h. However, the activity of the enzyme was greatly reduced in 90% methanol. The values of K and k2 for N‐benzyloxycarbonyl‐aspartic acid were 0·17 mol dm−3 and 11·9 mol dm−3 s−1 respectively.